IMPROVING THE QUALITY OF TEACHING RUSSIAN LANGUAGE AND LITERATURE BY MEANS OF FORMATIVE ASSESSMENT (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-130-144The study identifies the developing and motivating potential of formative assessment in the context of the updated Federal State Educational Standard for Basic General Education. Educational deficits that actualize the need to introduce criteria-based assessment at school are revealed. On the basis of the system-activity approach, criteria and indicators for assessing the level of students’ achievements in individual topics have been developed for current control. Tables of self-assessment of the achievements of students in the lessons of the Russian language and literature on the basis of criteria-based assessment have been developed to determine the level of formation of the educational and cognitive competence of schoolchildren, the relationship between the evaluation criteria and the requirements for the results of mastering the exemplary educational program in the Russian language and literature has been identified. The experience of implementing criteria-based assessment in the process of teaching the Russian language and literature proves that the work of students with self-assessment tables contributes to the development of meta-subject skills and the achievement of personal results, increases interest in learning and allows you to build an individual educational route for the student.Key words. Updated educational program, quality of education, activity approach, educational and cognitive competence forming assessment, criteria assessment, indicators, self-assessment tables